HUBUNGAN PENGETAHUAN DAN KECEMASAN TENTANG CORONA VIRUS DISEASE DENGAN PERILAKU UNTUK VAKSIN COVID-19 PADA IBU HAMIL - Gumiarti; Suprik Atin; Syiska Atik Maryanti (Akademi Kebidanan Aifa Husada Madura, 2023)
Covid-19 vaccination is a safe and effective approach to controlling the pandemic and in people to prevent COVID-19-related morbidity and mortality. Preliminary studies show that the vaccination target for pregnant women is 326 targets (the national target is 70% of the population), but until November 2021 the vaccination target for pregnant women only reaches 68 people (20.8%). This study aims to determine the relationship and anxiety about corona virus disease with behavior for the covid-19 vaccine in pregnant women. The research design used was correlational with a cross sectional approach. The population in this study were pregnant women in the Pakusari Health Center working area with a sample of 180 respondents using simple random sampling technique. The results of the statistical test using che square show that there is a relationship between knowledge about the corona virus disease and behavior for the covid-19 vaccine in pregnant women in the Pakusari Health Center Work Area (p value = 0.000; = 0.05; C = 0.573) and there is a relationship between variables independent with the dependent variable which means the relationship between coronavirus disease anxiety and behavior for the covid-19 vaccine in pregnant women in the Pakusar Health Center Work Area (p value = 0.000; = 0.05; C = 0.572). It is recommended for pregnant women to actively carry out and check with midwives to get clear and true information related to the covid-19 vaccination.